Spiderman vs. Doc Ock - Semper, John.; Arad, Avi.; Lee, Stan.; Daniel Barnes, Christopher; Hale, Jennifer; Marvel Characters, Inc.; Buena Vista Home Entertainment; Viva Video ([Burbank, Calif.] : Distributed by Buena Vista Home Entertainment ; Singapore Distributed by Videovan Entertainment Industries ; distributed in the Philippines by Viva Video, 2004)
Doctor Octavius was a scientist working on a new invention until the laboratory accident fused a set of mechanical arms to his body and turn him into the dreaded supervillain. "Doc Ock" seeks his revenge on those who did him wrong, and only Spiderman or his secret alter-ego, Peter Parker can put an end to his plan of destruction.
Previously released in 2003.
Doctor Octopus: Armed and dangerous / story by Avi Arad, Stan Lee --Partners in dangers. Chapter II, The cat ; Chapter III. The black cat ; Chapter V, Partners.
Animation directors, Frank Andrina [and others]; editor, C.K. Horness; story by John Semper; music, Shuki Levy, Kussa Manchi.
VCD
Keywords: Spider-Man -- (Fictitious character) -- Juvenile films; Animated television programs; Children's television programs